2020
DOI: 10.21608/ejchem.2020.26980.2555
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidines as Precursors for Synthesizing of Oxoketene gem-Dithiol and 1,2-Dithiol-3-Thione, a Facile Synthesis and Convenient Reaction Transformations

Abstract: In the present work the authors could synthesize the substrates oxoketene gem-dithols 5, ketene dithioacetal 6 and 1,2dithiol-3-thione 39 from compounds bearing both nucleus indole and dihydropyrimidines together due to their biological and pharmacological activities. In this paper, and as a result of biological and pharmacological activities of oxoketene gemdithiols, ketene dithioacetal and/or 1,2-dithiol-3-thione; we synthesized various derivatives of them via indole and dihydropyrimidine in the form of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Later on, it was shown that for some heterocyclic acetyl derivatives KH can be replaced by potassium tert-butoxide and hexamethyldisilathiane by P 2 S 5 (Scheme 6). In these cases, the yields may vary from good to low [37,38]. Unfortunately, it is still unclear whether this method is applicable to other ketones.…”
Section: Synthesis Of 3h-12-dithiole-3-thiones From α-Enolic Dithioesters and Related Compoundsmentioning
confidence: 99%
“…Later on, it was shown that for some heterocyclic acetyl derivatives KH can be replaced by potassium tert-butoxide and hexamethyldisilathiane by P 2 S 5 (Scheme 6). In these cases, the yields may vary from good to low [37,38]. Unfortunately, it is still unclear whether this method is applicable to other ketones.…”
Section: Synthesis Of 3h-12-dithiole-3-thiones From α-Enolic Dithioesters and Related Compoundsmentioning
confidence: 99%
“…Strong acidic conditions in a protic solvent [118,119] 2. Lewis's acids; strong Bronsted acids [120,121] 3.…”
mentioning
confidence: 99%